The important role of ferroptosis in inflammatory bowel disease - Xie, Hanhan; Cao, Chun; Shu, Dan; Liu, Tong; Zhang, Tao (Frontiers in Medicine, 2024)
Ferroptosis is a type of regulated cell death that occurs due to the iron-dependent accumulation of lethal reactive oxygen species (ROS) from lipids. Ferroptosis is characterized by distinct morphological, biochemical, and genetic features that differentiate it from other regulated cell death (RCD) types, which include apoptosis, various necrosis types, and autophagy. Recent reports show that ferritin formation is correlated to many disorders, such as acute injury, infarction, inflammation, and cancer. Iron uptake disorders have also been associated with intestinal epithelial dysfunction, particularly inflammatory bowel disease (IBD). Studies of iron uptake disorders may provide new insights into the pathogenesis of IBD, thereby improving the efficacy of medical interventions. This review presents an overview of ferroptosis, elucidating its fundamental mechanisms and highlighting its significant involvement in IBD.